Anorexia: Highlights in Traditional Persian medicine and conventional medicine - Majid Nimrouzi; Mohammad Mehdi Zarshenas (Mashhad University of Medical Sciences, 2017)
Objective: Anorexia and impaired appetite (Dysorexia) are common symptoms with varying causes, and often need no serious medical intervention. Anorexia nervosa (AN) is a chronic psychiatric disease with a high mortality rate. In Traditional Persian Medicine (TPM), anorexia is a condition in which anorexic patients lose appetite due to dystemperament. This review aims to discuss the common points of traditional and conventional approaches rather than introducing Persian medical recommendations suitable for nowadays use. Materialsand Methods: For this purpose, Avicenna's Canon of Medicine, main TPM resources and important databases were reviewed using the related keywords. Results: Despite complex hormonal explanation, etiology of AN in conventional approach is not completely understood. In TPM approach, the etiology and recommended interventions are thoroughly defined based on humoral pathophysiology. In TPM approach, disease states are regarded as the result of imbalances in organs' temperament and humors. In anorexia with simple dystemperament, the physician should attempt to balance the temperament using foods and medicaments which have opposite quality of temperament. Lifestyle, spiritual diseases (neuro - psychological) and gastrointestinal worms are the other causes for reducing appetite. Also, medicines and foods with warm temperaments (such as Pea soup and Mustard) are useful for these patients (cold temperament). Conclusion: Although the pathophysiology of AN in TPM is different in comparison with conventional views, TPM criteria for treatment this disorder is similar to those of current medicine. Recommending to have spiritual support and a healthy lifestyle are common in both views. Simple safe interventions recommended by TPM may be considered as alternative medical modalities after being confirmed by well-designed clinical trials.